Mixed convection casson fluid flow over an exponentially stretching sheet with Newtonian heating effect - Ahmad, Kartini; Wahid, Zaharah; Hanouf, Zahir (The Institute of Mechanics of Continua and Mathematical Sciences, 2019)
This paper deals with mixed convection of Casson fluid which flows over a heated surface that has been stretched exponentially. The governing equations that govern the fluid flow are reduced to ordinary differential equations by imposing suitable similarity variables. Numerical computational was carried out to solve for the f “(0) and θ (0) for some arbitrary values of the mixed convection parameter λ, Biot number Bi and Newtonian fluid parameter β when Pr =7.